2022
DOI: 10.3390/jintelligence10020027
|View full text |Cite
|
Sign up to set email alerts
|

Fluid Intelligence and Competence Development in Secondary Schooling: No Evidence for a Moderating Role of Conscientiousness

Abstract: Fluid intelligence and conscientiousness are important predictors of students’ academic performance and competence gains. Although their individual contributions have been widely acknowledged, less is known about their potential interplay. Do students profit disproportionately from being both smart and conscientious? We addressed this question using longitudinal data from two large student samples of the German National Educational Panel Study. In the first sample, we analyzed reading and mathematics competenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 68 publications
1
15
0
Order By: Relevance
“…Furthermore, a relevant topic concerns the question of how individual prerequisites shape the development of competences. The papers addressing this issue based on data from NEPS SC3 included cognitive (reasoning ability; Brandt & Lechner, 2022) or motivational predictors (Miyamoto et al, 2018(Miyamoto et al, , 2019, social behavior (prosocial behavior and peer problems; DeVries et al, 2021;life satisfaction;Lettau, 2021;Rathmann et al, 2018), personality traits (conscientiousness; Brandt & Lechner, 2022;Lechner et al, 2019) or gender-role orientation (Ehrtmann & Wolter, 2018) in order to explain competence levels and competence gains in secondary school students. For instance, Brandt and Lechner (2022) showed that reasoning ability as an indicator of fluid intelligence predicted the level and gains in reading and mathematical competences, whereas conscientiousness showed only small independent effects on competences.…”
Section: (4) Reuse Potentialmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, a relevant topic concerns the question of how individual prerequisites shape the development of competences. The papers addressing this issue based on data from NEPS SC3 included cognitive (reasoning ability; Brandt & Lechner, 2022) or motivational predictors (Miyamoto et al, 2018(Miyamoto et al, , 2019, social behavior (prosocial behavior and peer problems; DeVries et al, 2021;life satisfaction;Lettau, 2021;Rathmann et al, 2018), personality traits (conscientiousness; Brandt & Lechner, 2022;Lechner et al, 2019) or gender-role orientation (Ehrtmann & Wolter, 2018) in order to explain competence levels and competence gains in secondary school students. For instance, Brandt and Lechner (2022) showed that reasoning ability as an indicator of fluid intelligence predicted the level and gains in reading and mathematical competences, whereas conscientiousness showed only small independent effects on competences.…”
Section: (4) Reuse Potentialmentioning
confidence: 99%
“…In addition to analyzing the main effects of different predictors, the data also allowed for investigating interaction or mediating effects (e.g., Brandt & Lechner, 2022;Miyamoto et al, 2019) which, given the large number of constructs captured, gives multiple options for analysis that go beyond the available work.…”
Section: (4) Reuse Potentialmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from the impressive evidence for the unique contributions of fluid intelligence and conscientiousness in predicting success in school, these two factors may also interact meaningfully. Indeed, some studies have shown that intelligence and personality interact in the prediction of educational achievement (e.g., Bergold and Steinmayr 2018 ), whereas others could not find such an effect ( Brandt and Lechner 2022 ; Zhang and Ziegler 2015 ). In addition, different lines of reasoning argue for two distinct interaction processes.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, to date no study has investigated the potential longitudinal effects of intelligence-by-conscientiousness interactions on school grades, a highly relevant indicator of academic achievement, and could thus not model a potential interaction effect on the development of educational success. The majority of existing research also focuses on older students, using samples stemming from older adolescents or young adults from upper high school or university (but see, e.g., Brandt and Lechner 2022 ). The predictive value of intelligence, personality, and their interaction might be different in younger samples with a more diverse education background.…”
Section: Introductionmentioning
confidence: 99%